2012
DOI: 10.1186/2191-0855-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-N-acetylhexosaminidase (LeHex20A), a member of glycoside hydrolase family 20, from Lentinula edodes shiitake mushroom)

Abstract: We purified and cloned a β-N-acetylhexosaminidase, LeHex20A, with a molecular mass of 79 kDa from the fruiting body of Lentinula edodes (shiitake mushroom). The gene lehex20a gene had 1,659 nucleotides, encoding 553 amino acid residues. Sequence analysis indicated that LeHex20A belongs to glycoside hydrolase (GH) family 20, and homologues of lehex20a are broadly represented in the genomes of basidiomycetes. Purified LeHex20A hydrolyzed the terminal monosaccharide residues of β-N-acetylgalactosaminides and β-N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 43 publications
10
38
0
Order By: Relevance
“…These results show that speci c activity of CmNAGase toward Nacetyl COSs decreased when the degree of polymerization increased, which is similar with other reports [59]. The catalytic e ciency of GH20 LeHex20A from Lentinula edodes for (GlcNAc) 6 was greater than for (GlcNAc) 2 [60]. The GH20 NAGase VhNag2 from V. harveyi showed the highest activity against (GlcNAc) 4 , while the lowest activity was observed with (GlcNAc) 2 [61].…”
Section: The Substrate Speci City Of Cmnagasesupporting
confidence: 86%
See 3 more Smart Citations
“…These results show that speci c activity of CmNAGase toward Nacetyl COSs decreased when the degree of polymerization increased, which is similar with other reports [59]. The catalytic e ciency of GH20 LeHex20A from Lentinula edodes for (GlcNAc) 6 was greater than for (GlcNAc) 2 [60]. The GH20 NAGase VhNag2 from V. harveyi showed the highest activity against (GlcNAc) 4 , while the lowest activity was observed with (GlcNAc) 2 [61].…”
Section: The Substrate Speci City Of Cmnagasesupporting
confidence: 86%
“…Furthermore, CmNAGase showed some activity (0.02 U/mg) toward colloidal chitin. The result is similar with the GH20 NAGases from V. harveyi [61] and the fungal NAGases from Myceliopthora thermophila [62], L. edodes [60], and M. anisopliae [63], which were reported to degrade chitin to some extent without the cooperation of chitinase.…”
Section: The Substrate Speci City Of Cmnagasesupporting
confidence: 86%
See 2 more Smart Citations
“…This phenomenon shows that SYBC-H1 cells rupture during a long period of fermentation, which leads to the release of CmNAGase. To date, most reported NAGases are secretory proteins [21][22][23]. The results showed that the transport of N-acetyl COSs into the intracellular compartments of strain SYBC-H1 could be achieved by specific membrane transporters, then further hydrolyzed to GlcNAc by NAGase for cell growth, which is similar with other reports [24,25].…”
Section: Sybc-h1supporting
confidence: 82%